1997
DOI: 10.1139/z97-088
|View full text |Cite
|
Sign up to set email alerts
|

Total plasma protein level as an indicator of condition in wild American kestrels (Falco sparverius)

Abstract: Total plasma protein levels were determined for 292 female and 228 male American kestrels (Falco sparverius) in the wild. Plasma protein levels were significantly higher in females than in males, and higher during prelaying than during incubation. For both sexes, plasma protein levels did not vary significantly with the number of days before or after egg laying on which the sample was taken, time of sampling, prey abundance, age, molt, or infection by the blood parasite Haemoproteus sp. Protein levels in femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 30 publications
(24 reference statements)
0
30
1
Order By: Relevance
“…Total protein in plasma is the most stable component, and few dietary factors have been reported to affect the levels in fish. Plasma total protein is elevated when dietary protein intake increases (Leveille and Sauberlich, 1961) indicating improved physiological condition (Dawson and Bortolotti, 1997). Also, it has been suggested that increased blood protein level is associated with enhanced innate immune response in fish (Wiegertjes et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Total protein in plasma is the most stable component, and few dietary factors have been reported to affect the levels in fish. Plasma total protein is elevated when dietary protein intake increases (Leveille and Sauberlich, 1961) indicating improved physiological condition (Dawson and Bortolotti, 1997). Also, it has been suggested that increased blood protein level is associated with enhanced innate immune response in fish (Wiegertjes et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Totzke et al 1999;Quillfeldt et al 2004). Low levels of total proteins and triglycerides are often characteristic of short periods of food deprivation and covary with size-corrected body mass of birds (Boismenu et al 1992;Dawson and Bortolotti 1997;Guglielmo et al 2005). Also, plasma triglyceride concentrations have been widely used as indicators of mass gain and refuelling performance in shorebirds (Williams et al 1999;Seaman et al 2005).…”
Section: Plasma Protein and Triglyceridesmentioning
confidence: 99%
“…Total plasma protein levels may also become elevated when dietary protein intake increases (Leveille & Sauberlich 1961) and, thus, indicate improved physiological condition in wild birds (Dawson & Bortolotti 1997a). Total plasma protein can vary with sex and breeding stage and typically declines in nestlings as the breeding season progresses (Dawson & Bortolotti 1997a).…”
Section: Introductionmentioning
confidence: 99%